2008
DOI: 10.1354/vp.45-1-26
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Pituitary Histomorphometry with Adrenocorticotrophic Hormone Response to Domperidone Administration in the Diagnosis of Equine Pituitary Pars Intermedia Dysfunction

Abstract: Abstract. Functional evaluation of the pars intermedia (PI) is required for the early diagnosis of equine pituitary PI dysfunction (PPID), yet most assays target the hypothalamic-pituitary-adrenal axis, which regulates the pars anterior. In contrast, the PI is regulated by dopaminergic tone from hypothalamic neurons. Loss of dopaminergic inhibition is hypothesized to cause the PI hypertrophy and hyperplasia that result in the clinical manifestations of PPID. Domperidone, a dopamine receptor antagonist, should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
76
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 28 publications
6
76
0
2
Order By: Relevance
“…Unfortunately, since previous research has shown that histologic lesions in the pars intermedia do not always correlate with clinical signs [25], and since horses in the current study did not undergo diagnostic testing for PPID, the health implications of concurrent IR and pituitary lesions require further study. The results of this study, do, however, confirm previous reports that increasing pituitary scores are correlated with increasing age [18] [20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Unfortunately, since previous research has shown that histologic lesions in the pars intermedia do not always correlate with clinical signs [25], and since horses in the current study did not undergo diagnostic testing for PPID, the health implications of concurrent IR and pituitary lesions require further study. The results of this study, do, however, confirm previous reports that increasing pituitary scores are correlated with increasing age [18] [20].…”
Section: Discussionsupporting
confidence: 89%
“…The liver, pancreas, pituitary, and adrenal glands were collected, fixed in formalin, and evaluated microscopically for any lesions. Pituitaries were sectioned, evaluated microscopically, and scored according to published criteria (1, normal, to 5, macroadenoma) [18]. From complete cross sections of both the right and left adrenals, the adrenal cortical and medullary thicknesses were measured with an ocular micrometer.…”
Section: Necropsymentioning
confidence: 99%
“…Next, age‐associated decreases in hepatic and renal function could result in decreased insulin clearance, prolonging half‐life and duration of an increased circulating insulin concentration. Finally, although all aged mares had normal ODST results, this test is insensitive for detection of earlier stages of PPID . Thus, although differences in function of the hypothalamic–pituitary–adrenal axis between adult and aged mares cannot be excluded as an additional factor contributing to ID in aged horses, a recent study found no difference in glucose infusion rate during an isoglycaemic hyperinsulinaemic clamp in aged horses with and without PPID .…”
Section: Discussionmentioning
confidence: 93%
“…Case selection, with all PPID‐affected horses submitted for necropsy examination having PI macroadenomas, probably contributed to the diagnostic success of CT. In horses with less severe grades of PPID (PI hyperplasia or microadenoma formation) and minimal increase in overall pituitary gland size, CT imaging would be unlikely to detect these changes …”
Section: Discussionmentioning
confidence: 99%
“…These adenomas are thought to arise spontaneously . In contrast, PPID in horses is attributed to melanotrope hyperplasia and micro‐ and macro‐adenoma formation in the pituitary pars intermedia (PI) with resultant overproduction of pro‐opiomelanocortin (POMC) . Recent studies support a pathophysiology of PPID that may parallel that of Parkinson's disease: progressive degeneration of hypothalamic dopaminergic neurons associated with accumulation of aggregates of a misfolded protein, α‐synuclein, in nerve terminals .…”
mentioning
confidence: 99%